2017
DOI: 10.1108/jbim-09-2015-0169
|View full text |Cite
|
Sign up to set email alerts
|

Trust in marketing’s use of information from sales: the moderating role of power

Abstract: Purpose This paper aims to improve marketing managers’ use of information from sales. The authors propose and empirically test the link between cross-functional trust and marketing’s use of information from sales, and whether this effect is contingent on marketing’s power within the firm. Design/methodology/approach Cross-sectional survey data were collected from 338 large-scale Hungarian firms. Structural equation modeling and bootstrap procedures were used to test the hypotheses. Findings The effect of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 85 publications
1
20
0
Order By: Relevance
“…Other studies argue that product innovation strategy is crucial in satisfying customers' requirements (Arnett et al, 2018;Brown and Eisenhardt, 1997;Carbonell et al, 2012;Ravichandran, 2018;Yan et al, 2017). From an internal organisational perspective, interdepartmental collaboration is crucial for the organisation to adapt to and satisfy market dynamics (Hult, 2011;Keszey et al, 2017;Le Meunier-FitzHugh and Piercy, 2007;Le Meunier-FitzHugh and Lane, 2009;Lyus et al, 2011;Rouziès et al, 2005;Swink and Song, 2007;Turkulainen and Ketokivi, 2012). However, Chen et al (2014), Oosterhout et al (2006), Ravichandran (2018), Sambamurthy et al (2003), Tallon (2008) and Tallon and Pinsonneault (2011) examine the effect of IT capability and competency on business agility and firm performance.…”
Section: Business Process Agilitymentioning
confidence: 99%
“…Other studies argue that product innovation strategy is crucial in satisfying customers' requirements (Arnett et al, 2018;Brown and Eisenhardt, 1997;Carbonell et al, 2012;Ravichandran, 2018;Yan et al, 2017). From an internal organisational perspective, interdepartmental collaboration is crucial for the organisation to adapt to and satisfy market dynamics (Hult, 2011;Keszey et al, 2017;Le Meunier-FitzHugh and Piercy, 2007;Le Meunier-FitzHugh and Lane, 2009;Lyus et al, 2011;Rouziès et al, 2005;Swink and Song, 2007;Turkulainen and Ketokivi, 2012). However, Chen et al (2014), Oosterhout et al (2006), Ravichandran (2018), Sambamurthy et al (2003), Tallon (2008) and Tallon and Pinsonneault (2011) examine the effect of IT capability and competency on business agility and firm performance.…”
Section: Business Process Agilitymentioning
confidence: 99%
“…Prior studies on agility mainly focus on singular strategic focus, e.g. product innovation strategy perspective (Arnett et al, 2018;Brown and Eisenhardt, 1997;Ravichandran, 2018;Olsen and Sallis, 2006;Yan et al, 2017), market orientation (Han et al, 1998;Lin, 2004), interdepartmental collaboration (Hult, 2011;Keszey et al, 2017;Le Meunier-FitzHugh and Piercy, 2007;Le Meunier-FitzHugh and Lane, 2009;Turkulainen and Ketokivi, 2012), IT capability and competency (Chen et al, 2014;Oosterhout et al, 2006;Ravichandran, 2018;Sambamurthy et al, 2003;Tallon and Pinsonneault, 2011;Tallon, 2008). Teece et al (2016) explored agility at a more fundamental level and related it to dynamic capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Focusing on multiple categories of informants is considered suitable to enrich the understanding of organizational purchasing behavior (Kumar et al, 1993;Ronchetto et al, 1989) and to limit self-reported biases, which may not be congruent with reality, making research results questionable and unreliable (Silk and Kalwani, 1982;Crow and Lindquist, 1985;Kohli and Zaltman, 1988). In particular, besides buyers and users, we also decided involving truck sellers since, having adequate knowledge of purchasing (Keszey and Biemans, 2017) they were judged to be appropriate for both deepen the understanding of the phenomenon here studied and to cross-check findings gathered from other key informants. Since salespeople have frequent interaction with buyers and other organizational actors that take part to organizational purchasing, they are in a unique position to serve as a primary source of information (Gordon et al, 1997) On the suppliers' side, we interviewed 42 sales persons equally divided by brands.…”
Section: Methodsmentioning
confidence: 99%
“…A focus on multiple categories of informants is considered helpful to enrich understanding of organizational purchasing behavior (Kumar et al, 1993) and to limit self-reported biases, which may not be congruent with reality, making research results questionable and unreliable (Silk and Kalwani, 1982;Kohli and Zaltman, 1988). Besides buyers and users, we decided that it was important to involve truck sellers because their extensive knowledge of purchasing (Keszey and Biemans, 2017) means that they were judged to be appropriate for both deepening understanding of the phenomenon studied (Gordon et al, 1997), and triangulating findings from other key informants (Creswell and Clark, 2007).…”
Section: Methodsmentioning
confidence: 99%